The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.bbamem.2017.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Influence of glutamic acid residues and pH on the properties of transmembrane helices

Abstract: Negatively charged side chains are important for the function of particular ion channels and certain other membrane proteins. To investigate the influence of single glutamic acid side chains on helices that span lipid-bilayer membranes, we have employed GWALP23 (acetyl-GGALW5LALALALALALALW19LAGA-amide) as a favorable host peptide framework. We substituted individual Leu residues with Glu residues (L12E or L14E or L16E) and incorporated specific 2H-labeled alanine residues within the core helical region or near… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 39 publications
3
24
0
Order By: Relevance
“…At the next step of verification, we compared FMAP 2.0 predictions of TM and non-TM peptide arrangements in lipid bilayers with published experimental data. The test set 6 included synthetic pH-triggered membrane peptides with ionizable residues within hydrophobic α-helices studied by solid-state NMR, ATR-FTIR spectroscopy, and OCD , at different pH values (50 data points for 32 peptides). These peptides were designed to examine the pH-dependent equilibrium between membrane-spanning TM α-helices and surface-bound non-TM states in model PC bilayers .…”
Section: Resultsmentioning
confidence: 99%
“…At the next step of verification, we compared FMAP 2.0 predictions of TM and non-TM peptide arrangements in lipid bilayers with published experimental data. The test set 6 included synthetic pH-triggered membrane peptides with ionizable residues within hydrophobic α-helices studied by solid-state NMR, ATR-FTIR spectroscopy, and OCD , at different pH values (50 data points for 32 peptides). These peptides were designed to examine the pH-dependent equilibrium between membrane-spanning TM α-helices and surface-bound non-TM states in model PC bilayers .…”
Section: Resultsmentioning
confidence: 99%
“…Our in silico calculations unveiled that the protonated state of D150, rather than the deprotonated state, stabilized the trimeric structure in the membrane bilayer. It should be noted that several studies have shown that the membrane environment can modulate the p K a values of charged residues dramatically to the direction of being neutral (p K a of 7) since the microenvironment (dielectric constant) is changed from the bulk solution to the hydrophobic membrane. Therefore, it is not surprising that the measured p K a of D150 of TMD5 is 7.3–7.4, which is far from the p K a value (3.7) of Asp in water. Most likely the equilibrium shifts of D150 protonation states provide a mechanism for LMP-1 to manipulate its conformation and function in the different microenvironments of the host cell.…”
Section: Discussionmentioning
confidence: 97%
“…20,31−33 While small changes in the local fraying are detected easily by the highly sensitive 2 H NMR methods, such changes involving helix terminal disorder may not necessarily be reflected in the circular dichroism spectra. 20,31 Notably, the helix disorder, whether arising from changes in end fraying or orientations of the core helix, is lipid-dependent as well as pH-dependent as the detailed behavior varies among bilayers of DLPC, DMPC, and DOPC. These features will be important for understanding the plasticity of protein functional domains for which, notably, the cholesterol content also is a significant regulatory factor.…”
Section: ■ Discussionmentioning
confidence: 99%
“…As a further background, E16 alone confers spectral broadening with little or no pH dependence for the core helix orientation yet significant local unwinding at high pH. 20 We now examine the influence of E16 upon the very stable Arg-anchored R14 helix, acetyl-GGALW 5 LALALALAR 14 ALALW 19 LAGA-amide, in bilayer membranes. Notably, the Glu residue is placed on the opposite face of the helix from that of the Arg residue, with 200°(or 360−200°) radial separation (Figure 1).…”
Section: ■ Introductionmentioning
confidence: 99%